Interação universidade-escola através dos espaços museológicos: o pátio da ciência da UFG - Cruz, Lorena Nunes da (2016)
The non-formal spaces in which seeks to teach science content , by present ing a great scient ific potent ial , educat ional , cul tural and mul t iple communicat ion opt ions, can assist in this process, st imulat ing interest in discussions on th e topic discussed. This work was proposed to understand how a universi ty museum space, in this case the courtyard of the Science of the Federal Universi ty of Goiás, can cont ribute to the learning of elementary school students in science content . For i ts re al izat ion was used as target students in 9th grade at a school belonging to the Municipal Network of Educat ion Goiânia. As data col lect ion inst ruments, ini t ial and final reports were used, quest ionnaires, field diary and interviews. Thus, wi th the data ana lysis, we defined three stages, namely: data from ini t ial reports, data from quest ionnaires/ interviews and data of the final repor ts. It was possible to see the emergence of four categories based on the analysis of the ini t ial repor ts, namely: faci l i tat ing content , interdiscipl inary, mot ivat ion and relat ionship school -museum space. In the second phase (quest ionnaires and interviews), i t was observed that f rom the conceptual content , students were able to establ ish a relat ionship between procedural and at t i tudinal content in non- formal space, appear ing two subcategories: art iculat ion teacher /moni tor and care for the environment /Cheers. In the third stage ( final reports), the data only reinforced the categories that emerged f rom the ini t ial reports, quest ionnai res and interviews, but i t was observed that these met bet ter prepared when randomly compared wi th the fi rst report produced by the students. It can be observed that the classes obtained are not in isolat ion but inter related. So when the teacher engages in the act ivi t ies proposed in the planning together wi th the moni tors and staf f responsible for the space, the learning opportuni t ies increase. Thus, i t is intensified interact ion between the Universi ty and the Basic Educat ion wi thout occur dominat ion by ei ther party but a harmony between both, so that an inst i tut ion can complement the other, respect ing their part iculari t ies, assist ing students in thei r process teaching and learning.